Murabahah Financing Analysis for Civil Servants at PT. BPRS Fadhilah Bengkulu City - Elsi Apriliani; Wagini Wagini; Abdul Rahman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the implementation of murabahah financing for civil servants at PT. BPRS Fadhilah Bengkulu City is in accordance with the Statement of Financial Accounting Standards (PSAK) Number 102. Based on the results of the analysis of murabahah financing for Civil Servants (PNS) at BPRS Fadhilah Bengkulu it is very good and in accordance with PSAK 102. From the above discussion, we can see that murabahah financing creates buying and selling transactions in which the bank mentions the amount of profit. Murabahah financing will also provide awareness about the selling price, namely the bank's purchase price from the supplier plus profits, in banking murabahah financing also affects it in the sense that murabahah is usually carried out by means of installment payments (bi tsaman ajil). In this transaction, the goods are delivered immediately after the contract, while the payment is made on a deferred basis. Based on the results of this study, it can be concluded that BPRS Fadhilah Bengkulu is very good and in accordance with PSAK 102. From the above discussion we can see that both recognition and measurement, presentation and disclosure are almost in accordance with PSAK No. 102